2010
DOI: 10.1177/1741143209351831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Middle-level Leader and Teacher Emotional Intelligence on School Teachers’ Job Satisfaction

Abstract: Emotional intelligence (EI) has been an emerging topic for educational, psychological and management researchers and consultants in recent years. Despite the emerging consensus of its definition and evidence reported in business organizations, relatively little empirical evidence have been reported in the education literature. We conducted two studies to investigate the impact of middle-level leader and teacher EI on teachers’ job outcomes. In Study 1, 107 teachers were asked to list the attributes of successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 30 publications
2
49
0
7
Order By: Relevance
“…The other studies also have confirmed the relationship between organizational commitment and the EI [17,18]. In the study performed by Akbari Booreng et al, a significant relationship was also observed between organizational commitment and EI [19].…”
Section: Discussionmentioning
confidence: 65%
“…The other studies also have confirmed the relationship between organizational commitment and the EI [17,18]. In the study performed by Akbari Booreng et al, a significant relationship was also observed between organizational commitment and EI [19].…”
Section: Discussionmentioning
confidence: 65%
“…A negative relationship between EI and burnout and positive relationship between EI and job satisfaction was found by Platsidou (2010). Teachers with high EI is likely to experience grater job satisfaction (Wong et al, 2010). EI was significantly and positively related to job satisfaction and organizational commitment (Guleryuz et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…. and led to a lot of skepticism [sic]' (Wong et al 2010). So, Wong et al resurrect emotional intelligence in terms of four key aspects:…”
Section: Measuring Emotionmentioning
confidence: 99%
“…The Bar-On EQi (Bar-On 1997) is an example of a measurement inventory scale that deals not only with emotion and intelligence but also motivation, and what Wong, Wong, and Peng (2010) recently describe as 'motivation, non-ability dispositions and traits, and global and social functioning' (60). For these writers, such all encompassing approaches have detracted from EQi's 'scientific rigour as a distinct concept .…”
Section: Measuring Emotionmentioning
confidence: 99%